Bench Mark Survey of Thirty Four Community Development Blocks - Notes & Tables, Programme Evaluation Organisation, Planning Commission, Government of India - Planning Commission (Planning Commission, 1966)
In 1954-55, the P.E.O. had conducted, a Bench Mark Survey in 20 Community Development blocks with a special focus on the "position regarding acceptance of sponsored practices and certain aspects of the rural economy related to the development programmes as at the time of survey or for a given period immediately before it. Data for 18 of those blocks were analysed and Results were brought out in a number of P.E.O. publications. The results of this survey provided the-base line of the economic and social conditions in these areas, as in 1954-55. It was in the same 18 blocks that a repeat survey was Conducted in l959-60 and results were brought out in P.E.O. Publication No. 47. Along with this re-survey in 1959-60 a fresh Bench Mark Survey was conducted in another set of 34 development blocks. Since the first Bench Mark Survey in 1954-55, the number of blocks in the country has increased to about 2500. Due to phenomena expansion in development blocks in the country and with a view to provide wider sample for subsequent re-surveys, this fresh survey was conducted in 34 blocks.
Notes & Tables
Government of India